2018
DOI: 10.3748/wjg.v24.i4.511
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NUDT15 variants on hematological pictures of patients with inflammatory bowel disease treated with thiopurines

Abstract: AIMThe single nucleotide polymorphism (SNP) c.415C>T in exon 3 of NUDT15 affects thiopurine-induced leukopenia in Asian patients with Crohn’s disease. Meanwhile, three additional genetic variants of NUDT15 were reported in patients with acute lymphoblastic leukemia. We evaluated the effects of these additional genetic variants of NUDT15 in patients with inflammatory bowel disease (IBD) treated with thiopurines.METHODSNinety-six Japanese patients with IBD were enrolled. Genotyping for the NUDT15 and TPMT genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 20 publications
6
16
0
Order By: Relevance
“…Our study also showed that the MCV at each time point was significantly higher in the C/T group than in the C/C group, indicating that the red blood cells of patients heterozygous for the NUDT15 R139C variant are more sensitive than those of patients homozygous for the wild‐type allele. This result is consistent with a previous study reporting that MCV values at 10 weeks after initiating thiopurine were significantly higher in patients with the heterozygous variant alleles of NUDT15 than in those without . Several studies suggest that thiopurine‐mediated inhibition of DNA synthesis in bone marrow precursor cells leads to megaloblastic erythropoiesis .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our study also showed that the MCV at each time point was significantly higher in the C/T group than in the C/C group, indicating that the red blood cells of patients heterozygous for the NUDT15 R139C variant are more sensitive than those of patients homozygous for the wild‐type allele. This result is consistent with a previous study reporting that MCV values at 10 weeks after initiating thiopurine were significantly higher in patients with the heterozygous variant alleles of NUDT15 than in those without . Several studies suggest that thiopurine‐mediated inhibition of DNA synthesis in bone marrow precursor cells leads to megaloblastic erythropoiesis .…”
Section: Discussionsupporting
confidence: 92%
“…Kojima et al . observed that compared with patients with the variant, the WBC count became significantly lower at 6 weeks and remained lower through the remainder of the 16‐week study period in those with the variant . Although the WBC count beyond 16 weeks was not determined in their study, their WBC results up to this point are consistent with ours.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations